2020
DOI: 10.1177/1078390320905669
|View full text |Cite
|
Sign up to set email alerts
|

Substance Use and Exposure to Adverse Childhood Experiences in Undergraduate and Graduate Nursing Students

Abstract: BACKGROUND: Substance misuse remains a public health crisis and contributor to morbidity and mortality. The nursing workforce is not immune to the impacts of substance misuse as rates are thought to mirror those of the general population. Additionally, as substance misuse often begins in adolescence or early adulthood, prevalence of misuse among practicing nurses highlights the fact that students are also at risk. OBJECTIVES: The purpose of this study was to examine rates and patterns of substance use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 28 publications
(37 reference statements)
2
15
0
Order By: Relevance
“…This erosion of self‐worth and identity can make children more likely to use addictive substances at an early age than children of parents who did not use substances or did not have alternate support systems (Solis et al., 2012). Early exposure to substance use also increased the risk of addiction and premature death (Kameg et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…This erosion of self‐worth and identity can make children more likely to use addictive substances at an early age than children of parents who did not use substances or did not have alternate support systems (Solis et al., 2012). Early exposure to substance use also increased the risk of addiction and premature death (Kameg et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Merrick et al (2019) reported that 16% of adults surveyed experienced four or more ACEs, which are related to myriad poor health outcomes. Nursing students' ACE scores have also linked with SU; although findings are inconclusive (Kameg et al, 2020). In general, higher estimates of alcohol use risk were found in nursing students, but lower risks were assessed for drug use (20% moderate-to high-risk for alcohol; 3.6% moderate-to highrisk for drug use).…”
Section: Psychological Trauma As a Potential Risk Factormentioning
confidence: 99%
“…Despite this, the risk factors studied are not specific to nursing students. There is a profound paucity in the literature regarding to the prevalence of substance use among nursing students, as well as its risk factors [ 2 ]. Therefore, to reduce the risk of nursing students and later newly graduated nurses in the use of drugs, larger and long-term studies should be carried out to understand the factors that influence the use of illicit drugs in nursing students, including the previously mentioned variables, so as to facilitate the implementation of evidence-based interventions within nursing schools [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…The consumption of illicit drugs represents an important public health problem worldwide [ 1 ], contributing to morbidity and mortality [ 2 ]. Nowadays, Europe has one of the highest percentages of students who reported lifetime use of any illicit drug, with 29% in the Czech Republic, followed by 28% in Italy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation